2009
DOI: 10.1111/j.1742-4658.2009.07006.x
|View full text |Cite
|
Sign up to set email alerts
|

ThermoFAD, a Thermofluor®‐adapted flavin ad hoc detection system for protein folding and ligand binding

Abstract: In living organisms, genes encoding proteins that contain flavins as a prosthetic group constitute approximately 2–3% of the total. The fluorescence of flavin cofactors in these proteins is a property that is widely employed for biochemical characterisation. Here, we present a modified Thermofluor® approach called ThermoFAD (Thermofluor®‐adapted flavin ad hoc detection system), which simplifies identification of optimal purification and storage conditions as well as high‐affinity ligands. In this technique, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
212
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(217 citation statements)
references
References 30 publications
4
212
0
1
Order By: Relevance
“…[14] This confirmed that AcCHMO is only moderately stable since it exhibits a T m value of 37 8 8C (Table S4).…”
supporting
confidence: 65%
“…[14] This confirmed that AcCHMO is only moderately stable since it exhibits a T m value of 37 8 8C (Table S4).…”
supporting
confidence: 65%
“…The unfolding temperatures of purified HMFO, SUMO-HMFO, and the SUMO-HMFO H467A mutant enzyme were analyzed by the ThermoFAD method (17). By this method, the release of the flavin cofactor is monitored while heating the enzyme.…”
Section: Methodsmentioning
confidence: 99%
“…In order to check if the PAMO mutants lost significant thermostability due to the mutations, T m values were measured the ThermoFAD method (Forneris et al, 2009). …”
Section: Thermostability Of Wt Pamo and Evolved Mutantsmentioning
confidence: 99%